The combined effect of H2O and SO2 on the simultaneous calcination/sulfation reaction in CFBs - Chen, Liang; Wang, Chunbo; Zhao, Fan; Zou, Chan; Anthony, Edward J. (Wiley, 2019)
The combined effect of H2O and SO2 on the reaction kinetics and pore structure of limestone during simultaneous calcination/sulfation reactions under circulating fluidized bed (CFB) conditions was first studied in a constant‐temperature reactor. H2O can accelerate the sulfation reaction rate in the slow‐sulfation stage significantly but has a smaller effect in the fast‐sulfation stage. H2O can also accelerate the calcination of CaCO3, and should be considered as a catalyst, since the activation energy for the calcination reaction was lower in the presence of H2O. When the limestone particles are calcining, SO2 in the flue gas can react with CaO on the outer particle layer and the resulting CaSO4 blocks the CaO pores, increases the diffusion resistance of CO2 and, in consequence, decreases the calcination rate of CaCO3. Here, gases containing 15% H2O and 0.3% SO2 are shown to increase the calcination rate. This means that the accelerating effect of 15% H2O on CaCO3 decomposition is stronger than the impeding effect caused by 0.3% SO2. The calcination rate of limestone particles was controlled by both the intrinsic reaction and the CO2 diffusion rate in the pores, but the intrinsic reaction rate played a major role as indicated by the effectiveness factors determined in this work. This may explain the synergic effect of H2O and SO2 on CaCO3 decomposition observed here. Finally, the effect of H2O and SO2 on sulfur capture in a 600 MWe CFB boiler burning petroleum coke is also analyzed. The sulfation performance of limestone evaluated by simultaneous calcination/sulfation is shown to be much higher than that by sulfation of CaO. Based on our calculations, a novel use of the wet flue gas recycle method was put forward to improve the sulfur capture performance for high‐sulfur, low‐moisture fuels such as petroleum coke.
Keywords: Calcination; Sulfation; Simultaneous reaction; Limestone; Kinetics; H2O